Correlation of the TTQ (Tartil and Tahfidz Al-Qur'an) Program and Learning Outcomes of Students in Al-Qur'an Hadith Subjects at MTs Mutaallimin Patokbeusi Subang Regency - Hanifah, Nur; Solihatudiniyah, Lela Salamah; Ihsan, Muhammad; Tarsono, Tarsono (CV. Rayyan Dwi Bharata, 2024)
The Koran is the main source of law in the teachings of the Islamic religion. The Qur'an is the best reading material and reading it is a form of worship. This research aims to determine the relationship between the TTQ (Tartil and Tahfidz Al-Qur'an) program and the learning outcomes of students in Al-Qur'an hadith subjects. This research uses a quantitative approach with a correlation design carried out at MTs Mutaallimin Patokbeusi, Bandung Regency. And the data collection used is tests and document studies. The research results show that the sig value that connects TTQ learning outcomes and Al-Qur'an Hadith learning outcomes is 0.000. This sig value is smaller than 0.05 so Ho is rejected or H1 is accepted, and it can be concluded that